Co-composting of sewage sludge and Phragmites australis using different insulating strategies. (1st May 2020) - Hu, Jiahui; Yang, Zhaohui; Huang, Zhongliang; Li, Hui; Wu, Zijian; Zhang, Xuan; Qin, Xiaoli; Li, Changzhu; Ruan, Min; Zhou, Kang; Wu, Xikai; Zhang, Yanru; et al.
Graphical abstract: Highlights: Insulating strategy notably influenced the laboratory-scale composting behaviors. A centre oriented real-time temperature compensation was applied in the composting. Five composting reactors with different insulating strategies were compared. Co-composting of sludge and wetland plants is meaningful for the running of WWTP. Abstract: Insulating strategies are indispensable for laboratory-scale composting reactors, however, current insulation methods interfere with the aerobic fermentation behaviors related to composting. To address this issue, a centre-oriented real-time temperature compensation strategy was designed in this study. Five 9 L reactors (R1–R5) with different insulation strategies were used for the co-composting of dewatered sludge and Phragmites australis and compared. The process performance was assessed by monitoring the temperature, O2 and CO2 emissions, the physical–chemical properties of the composting materials were evaluated by measuring the organic matter (OM), carbon nitrogen ratio (C/N), pH, electrical conductivity (EC), and fluorescence excitation-emission matrix (EEM) spectra. And a 16S rDNA analysis was used to quantify the evolution of bacterial community. The main findings are as follows. Compared with R1 as a control, the insulating strategies can increase the maximum temperature and prolong the thermophilic phase of composting. Comparing R1 and R3 showed that real-time temperature compensation can better restore the real fermentation of the compost. The results showed that R5 had the best composting effect, reaching 69.8 °C, which was 25.1%, 29.7%, 19.3%, and 17.3% higher than R1, R2, R3, and R4, respectively, and remaining in the thermophilic phase for 4.24 d, which is 1.4, 1.5, 1.3, and 0.2 times longer than R1, R2, R3, and R4, respectively. Furthermore, it can significantly reduce the temperature difference between the centre and edge of the reactor, which improved the composting material allocation efficiency and composting process control accuracy, further providing a basis for the actual full-scale composting operation.